Pengaruh Modal Usaha, Kreativitas, dan Gaya Kepemimpinan Terhadap Keberhasilan Usaha Badan Usaha Milik Desa “Unggul Makmur Sejahtera” Desa Sungonlegowo Bungah Gresik - Zaidatur Rohmah, Niswatun Hasanah, (Jurnal Qiema (Qomaruddin Islamic Economics Magazine), 2024)
This study aims to determine: (1) The partial effect of business capital on the success of BUMDes businesses in Sungonlegowo Village, (2) The partial effect of creativity on the success of BUMDes businesses in Sungonlegowo Village, (3) The partial effect of leadership style on the success of BUMDes businesses in Sungonlegowo Village, ( 4) The effect of business capital, creativity and leadership style simultaneously on the success of the BUMDes business in Sungonlegowo Village. This research uses quantitative methods. The population in this study were village officials, BPD, heads of RT, heads of RW, and BUMDes employees. The sampling technique uses probability sampling with a total sample of 50 respondents, data collection techniques through observation, questionnaire documentation (questionnaire), data analysis using multiple linear regression and data processing using SPSS software version 22. The results showed that: (1) The results of business capital on the success of the business carried out by 50 respondents, have a partial influence on business success because business capital has a significance value of 0.000, less than 0.05. So that the venture capital variable influences business success, (2) The results of creativity on business success carried out on 50 respondents, have a partial influence on business success because creativity has a significance value of 0.000 less than 0.05. So that the creativity variable influences business success, (3) The results of leadership style on business success carried out on 50 respondents, have a partial influence on business success because creativity has a significance value of 0.000 less than 0.05. So that the creativity variable affects the payment of zakat, (4) Simultaneously the variables of business capital, creativity, and leadership style affect business success with the value of the f table test results obtained with a sig value of 0.000 less than 0.05 which means Ho is rejected and Ha is accepted.